New method of Scoliosis Deformity Assessment: ISIS2 System. - Zubović, A; Davies, N; Berryman, F; Pynsent, P; Quraishi, N; Lavy, C; Bowden, G; Wilson-Macdonald, J; Fairbank, J (2008)
Scoliosis deformity has been assessed using radiographic angle measurements. Surface topography systems are an alternative and complementary methodology. Working systems include the original ISIS1 system, Quantec and COMOT techniques. Over the last five years the new ISIS2 (Integrated Shape Imaging System) has been developed from basic principles to improve the speed, accuracy, reliability and ease of use of ISIS1. The aim of this study was to confirm that ISIS2 3D back shape measurements are valid for assessment and follow up of patients with scoliosis. Three-dimensional back measurements were performed in Oxford. ISIS2 includes a camera/projector stand, patient stand with a reference plane, and Mac computer. Pixel size is approximately 0.5 mm with fringe frequency of approximately 0.16 fringes/mm ( approximately 6.5 mm/fringe). Clinical reports in pdf format are of coloured images with numerical values. Reports include a height map, contour plot, transverse section plots, coronal plot, sagittal sections and bilateral asymmetry maps. A total of 520 ISIS2 scans on 242 patients were performed from February 2006 to December 2007. There were 58 male patients (median age 16 years, SD 3.71, min 7, max 25) and 184 female patients (median age 14.5 years, SD 3.23, min 5, max 45). Average number of scans per patient was 2.01 with the range of 1-10 scans. Right sided thoracic curves were the most frequent pattern. The median values and 95% CI are reported of back length; pelvic rotation; flexion/extension; imbalance; lateral asymmetry; skin angle; kyphosis angle; lordosis angle; volumetric asymmetry. ISIS2 scoliosis measurements are non-invasive, low-cost, three-dimensional topographic back measurements which can be confidently used in scoliosis assessment and monitoring of curve progression.